Comorbidities, timing of treatments, and chemotherapy use influence outcomes in stage III colon cancer: A population-based European study. Issue 6 (June 2020) - ,; Van Eycken, L.; Henau, K.; Grozeva, T.; Valerianova, Z.; Innos, K.; Mägi, M.; Bouvier, V.; Launoy, G.; Jooste, V.; Normand, S.; Robaszkiewicz, M.; et al.
Abstract: Introduction: For stage III colon cancer (CC), surgery followed by chemotherapy is the main curative approach, although optimum times between diagnosis and surgery, and surgery and chemotherapy, have not been established. Materials and methods: We analysed a population-based sample of 1912 stage III CC cases diagnosed in eight European countries in 2009–2013 aiming to estimate: (i) odds of receiving postoperative chemotherapy, overall and within eight weeks of surgery; (ii) risks of death/relapse, according to treatment, Charlson Comorbidity Index, time from diagnosis to surgery for emergency and elective cases, and time from surgery to chemotherapy; and (iii) time-trends in chemotherapy use. Results: Overall, 97% of cases received surgery and 65% postoperative chemotherapy, with 71% of these receiving chemotherapy within eight weeks of surgery. Risks of death and relapse were higher for cases starting chemotherapy with delay, but better than for cases not given chemotherapy. Fewer patients with high comorbidities received chemotherapy than those with low ( P  < 0.001). Chemotherapy timing did not vary ( P  = 0.250) between high and low comorbidity cases. Electively-operated cases with low comorbidities received surgery more promptly than high comorbidity cases. Risks of death and relapse were lower for elective cases given surgery after four weeks than cases given surgery within a week. High comorbidities were always independently associated with poorer outcomes. Chemotherapy use increased over time. Conclusions: Our data indicate that promptly-administered postoperative chemotherapy maximizes its benefit, and that careful assessment of comorbidities is important before treatment. The survival benefit associated with slightly delayed elective surgery deserves further investigation. Highlights: Practically all stage III colon cancer cases received surgery, 65% of these received postoperative chemotherapy Fewer high comorbidity cases received prompt elective surgery or received chemotherapy Receiving surgery ≤4 weeks from diagnosis was associated with poorer outcomes Starting chemotherapy >8 weeks from surgery was associated with poorer outcomes High comorbidities were independently associated with poorer outcomes